2014
DOI: 10.1016/j.scitotenv.2013.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Organic micropollutants in the Yangtze River: Seasonal occurrence and annual loads

Abstract: • The Yangtze River drains 40% of China's mainland with 400 million inhabitants • Monthly concentrations and annual loads of organic pollutants were determined • Seasonality of loads of PAHs, most pesticides, and antiinfectives were concise • In spite of low concentrations due to high water discharge, pollutant loads are considerable a b s t r a c t a r t i c l e i n f o Twenty percent of the water run-off from China's land surface drains into the Yangtze River and carries the sewage of approximately 400 milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 65 publications
(80 reference statements)
1
43
1
Order By: Relevance
“…High dilution and fast metabolism of these compounds in the environment may explain the lower concentrations observed in surface water. All other pharmaceutical active compounds observed in this study have already been reported either in surface waters or in the influent/effluent of wastewater treatment plants in China (Bu et al 2013;Heeb et al 2012;Liu and Wong 2013;Qi et al 2014). Values for carbamazepine and diclofenac which were determined in this study with higher mean abundance have been reported in surface water in China with concentration ranges from nondetection to 675 and nondetection to 843 ng L −1 , respectively (Bu et al 2013).…”
Section: Analysis Of Pharmaceuticals and Polar Herbicidessupporting
confidence: 68%
See 4 more Smart Citations
“…High dilution and fast metabolism of these compounds in the environment may explain the lower concentrations observed in surface water. All other pharmaceutical active compounds observed in this study have already been reported either in surface waters or in the influent/effluent of wastewater treatment plants in China (Bu et al 2013;Heeb et al 2012;Liu and Wong 2013;Qi et al 2014). Values for carbamazepine and diclofenac which were determined in this study with higher mean abundance have been reported in surface water in China with concentration ranges from nondetection to 675 and nondetection to 843 ng L −1 , respectively (Bu et al 2013).…”
Section: Analysis Of Pharmaceuticals and Polar Herbicidessupporting
confidence: 68%
“…Pharmaceuticals were detected between 2009 and 2010 near Datong (600 km from the East China Sea) at concentrations usually below 50 ng L −1 . Furthermore, other household chemicals were detected, especially the sweetener sucralose which occurred at an average concentration of 217 ng L −1 (Qi et al 2014). The distribution pattern of PPCPs within the TGR is comparable to PFCs which are emitted by point sources.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations